Outcome of Unstable Thoracolumbar Fracture Following Long Segment Posterior Fixation (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Fractures of the thoracolumbar region are the most common injuries of the vertebral column and burst fractures are the most frequent. The purpose of this study was to see the radiological and functional outcome after long segment posterior fixation in unstable thoracolumbar spine injury with incomplete neurological deficit.Methods: A total of 146 cases were included in this prospective case series from January 2014 to December 2018 through non randomized purposive sampling. All the patients were operated with long segment posterior fixation and postero-lateral fusion by Autogenous cancellous bone graft. Postoperative functional outcome was assessed both clinically by ODI, VAS, ASIA and radiologically by Bridwell criteria. Postoperative follow up was conducted at 2nd, 6th,12th and finally 6 monthly.Results: The mean Cobb angle at pre-operative was 21.5 ±8.9 and at final follow-up was 11±4.57 in this study (p-value